Realizing Near‐Infrared Laser Dyes through a Shift in Excited‐State Absorption (Advanced Optical Materials 6/2021). Issue 6 (19th March 2021) - Aoki, Reiko; Komatsu, Ryutaro; Goushi, Kenichi; Mamada, Masashi; Ko, Soo Young; Wu, Jeong Weon; Placide, Virginie; D'Aléo, Anthony; Adachi, Chihaya
Abstract : The cover image shows organic semiconductor materials for near‐infrared lasers, referring to article number 2001947 by Masashi Mamada, Anthony D'Aléo, Chihaya Adachi and co‐workers. Based on their core structure, the complete organic emitters are classified as curcuminoids, which are analogues of the curcumin dye found in turmeric. Rational modification of the chemical structure enables bright near‐infrared emission and lasing as well as thermally activated delayed fluorescence. The work represents a promising approach for developing materials for near‐infrared organic electronic devices.